2002
DOI: 10.1093/jxb/erf020
|View full text |Cite
|
Sign up to set email alerts
|

Semi-volatile organic compounds at the leaf/atmosphere interface: numerical simulation of dispersal and foliar uptake

Abstract: The behaviour of (semi-)volatile organic compounds at the interface between the leaf surface and the atmosphere was investigated by finite-element numerical simulation. Three model systems with increasing complexity and closeness to the real situation were studied. The three-dimensional model systems were translated into appropriate grid structures and diffusive and convective transport in the leaf/atmosphere interface was simulated. Fenpropimorph (cis-4-[3-(4-tert-butylphenyl)-2-methylpropyl]-2,6-dimethylmorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Leaf properties such as the thickness of the cuticular wax layer, as well as volatility and polarity (Riederer et al, 2002) of the volatile compound in question, and environmental conditions such as wind, light, humidity and temperature (Niinemets et al, 2004) affect the adsorption of volatiles from surrounding air to leaves. The volatility and lipophilicity of plant-emitted volatile compounds vary substantially (Noe et al, 2006(Noe et al, , 2008.…”
Section: Persistence Of Volatiles -How Variable Is It?mentioning
confidence: 99%
“…Leaf properties such as the thickness of the cuticular wax layer, as well as volatility and polarity (Riederer et al, 2002) of the volatile compound in question, and environmental conditions such as wind, light, humidity and temperature (Niinemets et al, 2004) affect the adsorption of volatiles from surrounding air to leaves. The volatility and lipophilicity of plant-emitted volatile compounds vary substantially (Noe et al, 2006(Noe et al, , 2008.…”
Section: Persistence Of Volatiles -How Variable Is It?mentioning
confidence: 99%
“…Thus, the barrier function of the cuticles seems to be very limited. Riederer and his colleagues 21 proposed a two-compartment sorption model in which the cuticle was divided into wax and cuticular matrix and was believed to have no significant effect on the sorption capacities after dewaxing. The fundamental principles of the two models were compared, and an obvious contradiction emerged in terms of the contributions of the cuticle components to accumulation.…”
mentioning
confidence: 99%
“…Kumar et al (2005a) showed that a macrolide antibiotic (tylosin, MW = 916) was not taken up by plants, compared with tetracycline‐class antibiotics (MW <500) that were taken up by plants. A similar relationship exists between skin permeability and the MW of pharmaceutical compounds, i.e., the higher the MW the lower the permeability (Potts and Guy, 1995; Sartorelli et al, 1998). In addition to octanol–water partitioning, Bunge and Cleek (1995) also highlighted the importance of MW in controlling the permeability of the stratum corneum and the epidermis in human skin.…”
Section: Physicochemical Properties Of Pharmaceutical Compounds Affecmentioning
confidence: 76%
“…Similar to solute uptake by plants, human drug absorption is also a passive diffusion mechanism, and thus both the physicochemical properties of the drug and the permeation barrier of membranes are the major rate determinants for its transport (Potts and Guy, 1995). In general, the structure of plant and mammalian cell membranes is similar and composed of a lipid bilayer and shown in Fig.…”
Section: Processes Of Uptake In Plants and Humansmentioning
confidence: 99%
See 1 more Smart Citation